Characteristics of Sexually Transmitted Infections in Patients with Human Immunodeficiency Virus /Acquired Immunodeficiency Syndromeat Abepura Regional Hospital: A Descriptive Study - Inneke Viviane Sumolang; Lusye Howay; Maria Novia Herlin Solossa (International Journal of Public Health Excellence (IJPHE), 2026)
Sexually Transmitted Infections (STIs) are a public health problem that remains a global challenge, especially for people with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS).  The relationship between HIV and STIs is bidirectional, where STIs can increase the risk of HIV transmission through genital mucosal damage and inflammatory processes, while a decreased immune system in HIV patients can worsen the manifestations of STIs. Papua is one of the provinces with a high number of HIV/AIDS cases in Indonesia, so it is important to understand the types of STIs and the factors that contribute to the occurrence of STIs in people with HIV/AIDS. This study aims to determine the most common types of STIs and the characteristic factors that contribute to the incidence of STIs in HIV/AIDS patients at the VCT Clinic of Abepura Regional Hospital for the period 2022–2024. Methods: This study used a quantitative approach with a descriptive design. The study sample consisted of 63 medical records of HIV/AIDS patients with STIs selected using a purposive sampling technique. Data were collected through a review of medical record documents and analyzed descriptively using frequency distribution and crosstabulation. The results showed that the most common type of STI found was syphilis with 55 cases (87.3%), followed by gonorrhea with 5 cases (7.9%) and condyloma acuminata with 3 cases (4.8%). The majority of patients were in the 17–25 years age group (39.7%), male (55.6%), had a high school education (81%), were unemployed (34.9%), single (63.5%), and had high-risk sexual behavior (84.1%). No patients were found with a history of drug use. Conclusion: Syphilis was the most prevalent STI among HIV/AIDS patients at the VCT Clinic at Abepura Regional Hospital. The most common characteristics among HIV/AIDS patients with STI coinfection were young age, male gender, secondary education, single status, unemployed, and high-risk sexual behavior